If the question is how many students are girls, than it's ten(10).
Answer:
The equation of the parallel line is
y = 3x + 9
Step-by-step explanation:
The general equation of a straight line is given as;
y = mx + c
where m is the slope and c is the intercept
If two lines are parallel, their slopes are equal
So the slope of the new line too is 3
Using the point-slope formula
y-y1 = m(x-x1)
y-12 = 3(x-1)
y-12 = 3x-3
y = 3x-3 + 12
y = 3x + 9
B. 46 feet because 132/12=11 and 12+12+11+11=46
Answer:
100 boys at the concert
Step-by-step explanation:
When changing the ratio between the number of boys to the number of girls, it always has to be equivalent to the original ratio 2:7
So, convert the ratio 2:7 to a different ratio, but it still has to be equivalent to the ratio 2:7. By doing that, multiply both sides of the 2:7 ratio by 50:
2 : 7
×50 ×50
To get:
100:350 ⇒ This ratio means that the ratio between the number of boys to the number of girls is now 100:350, but that’s okay to have because it’s still equivalent to the original 2:7 ratio.
So, using the new ratio 100:350, this means that there are 100 boys at the concert and 350 girls at the concert, and 350 is 250 more than 100 which proves what the question is asking. So there are 100 boys at the concert.
<u>Answer:</u> 100 boys at the concert
<em>I hope you understand and that this helps with your question! </em>:)
I don't know what method is referred to in "section 4.3", but I'll suppose it's reduction of order and use that to find the exact solution. Take
![z=y'](https://tex.z-dn.net/?f=z%3Dy%27)
, so that
![z'=y''](https://tex.z-dn.net/?f=z%27%3Dy%27%27)
and we're left with the ODE linear in
![z](https://tex.z-dn.net/?f=z)
:
![y''-y'=0\implies z'-z=0\implies z=C_1e^x\implies y=C_1e^x+C_2](https://tex.z-dn.net/?f=y%27%27-y%27%3D0%5Cimplies%20z%27-z%3D0%5Cimplies%20z%3DC_1e%5Ex%5Cimplies%20y%3DC_1e%5Ex%2BC_2)
Now suppose
![y](https://tex.z-dn.net/?f=y)
has a power series expansion
![y=\displaystyle\sum_{n\ge0}a_nx^n](https://tex.z-dn.net/?f=y%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7Da_nx%5En)
![\implies y'=\displaystyle\sum_{n\ge1}na_nx^{n-1}](https://tex.z-dn.net/?f=%5Cimplies%20y%27%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge1%7Dna_nx%5E%7Bn-1%7D)
![\implies y''=\displaystyle\sum_{n\ge2}n(n-1)a_nx^{n-2}](https://tex.z-dn.net/?f=%5Cimplies%20y%27%27%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7Dn%28n-1%29a_nx%5E%7Bn-2%7D)
Then the ODE can be written as
![\displaystyle\sum_{n\ge2}n(n-1)a_nx^{n-2}-\sum_{n\ge1}na_nx^{n-1}=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7Dn%28n-1%29a_nx%5E%7Bn-2%7D-%5Csum_%7Bn%5Cge1%7Dna_nx%5E%7Bn-1%7D%3D0)
![\displaystyle\sum_{n\ge2}n(n-1)a_nx^{n-2}-\sum_{n\ge2}(n-1)a_{n-1}x^{n-2}=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7Dn%28n-1%29a_nx%5E%7Bn-2%7D-%5Csum_%7Bn%5Cge2%7D%28n-1%29a_%7Bn-1%7Dx%5E%7Bn-2%7D%3D0)
![\displaystyle\sum_{n\ge2}\bigg[n(n-1)a_n-(n-1)a_{n-1}\bigg]x^{n-2}=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7D%5Cbigg%5Bn%28n-1%29a_n-%28n-1%29a_%7Bn-1%7D%5Cbigg%5Dx%5E%7Bn-2%7D%3D0)
All the coefficients of the series vanish, and setting
![x=0](https://tex.z-dn.net/?f=x%3D0)
in the power series forms for
![y](https://tex.z-dn.net/?f=y)
and
![y'](https://tex.z-dn.net/?f=y%27)
tell us that
![y(0)=a_0](https://tex.z-dn.net/?f=y%280%29%3Da_0)
and
![y'(0)=a_1](https://tex.z-dn.net/?f=y%27%280%29%3Da_1)
, so we get the recurrence
![\begin{cases}a_0=a_0\\\\a_1=a_1\\\\a_n=\dfrac{a_{n-1}}n&\text{for }n\ge2\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da_0%3Da_0%5C%5C%5C%5Ca_1%3Da_1%5C%5C%5C%5Ca_n%3D%5Cdfrac%7Ba_%7Bn-1%7D%7Dn%26%5Ctext%7Bfor%20%7Dn%5Cge2%5Cend%7Bcases%7D)
We can solve explicitly for
![a_n](https://tex.z-dn.net/?f=a_n)
quite easily:
![a_n=\dfrac{a_{n-1}}n\implies a_{n-1}=\dfrac{a_{n-2}}{n-1}\implies a_n=\dfrac{a_{n-2}}{n(n-1)}](https://tex.z-dn.net/?f=a_n%3D%5Cdfrac%7Ba_%7Bn-1%7D%7Dn%5Cimplies%20a_%7Bn-1%7D%3D%5Cdfrac%7Ba_%7Bn-2%7D%7D%7Bn-1%7D%5Cimplies%20a_n%3D%5Cdfrac%7Ba_%7Bn-2%7D%7D%7Bn%28n-1%29%7D)
and so on. Continuing in this way we end up with
![a_n=\dfrac{a_1}{n!}](https://tex.z-dn.net/?f=a_n%3D%5Cdfrac%7Ba_1%7D%7Bn%21%7D)
so that the solution to the ODE is
![y(x)=\displaystyle\sum_{n\ge0}\dfrac{a_1}{n!}x^n=a_1+a_1x+\dfrac{a_1}2x^2+\cdots=a_1e^x](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%5Cdfrac%7Ba_1%7D%7Bn%21%7Dx%5En%3Da_1%2Ba_1x%2B%5Cdfrac%7Ba_1%7D2x%5E2%2B%5Ccdots%3Da_1e%5Ex)
We also require the solution to satisfy
![y(0)=a_0](https://tex.z-dn.net/?f=y%280%29%3Da_0)
, which we can do easily by adding and subtracting a constant as needed: